Pelvic peritoneal endometriosis is linked to the endometrial inflammatory profile: a prospective cohort study - Iwona Gawron; Kamil Derbisz; Robert Jach; Dominika Trojnarska; Katarzyna Milian-Ciesielska; Milosz Pietrus (BMC Women's Health)
Abstract Background Pelvic endometriosis is an estrogen-driven inflammatory syndrome of unknown origin that alters the peritoneal microenvironment and likely impairs endometrial receptivity, adversely affecting fertility. Chronic endometritis (CE) may be a potential contributing factor to reduced endometrial receptivity in endometriosis. The aim of the study was to analyze the correlation between pelvic endometriosis and CE. Methods The study included women undergoing laparoscopy for suspected pelvic endometriosis, and each underwent endometrial aspiration biopsy for CE. The stage of endometriosis was assessed intraoperatively, and CE activity was evaluated histopathologically and immunohistochemically. The associations between selected clinical characteristics of the disease and the density of endometrial plasma cells, immunohistochemical status, and histopathological profile of the endometrium were analyzed. Results Stage III endometriosis reduced the risk of the inflammatory immunohistochemical profile by 80% (OR = 0.18, p = 0.037) when compared to Stage I. Peritoneal endometriosis was associated with a 3.429-fold increase in the risk of the immunohistochemical endometrial inflammatory profile (OR = 3.429, p = 0.038). No significant associations were found between the clinical features of the disease and plasma cell density or the histopathological profile of the endometrium (all p values > 0.05). No significant differences were observed in IVF use (p = 0.67), pregnancy rates (p = 1), or live birth rates (p = 0.41) between infertile women with and without CE. Conclusions Should peritoneal endometriosis be diagnosed during a laparoscopy conducted for the treatment of infertility, it is advisable to obtain an endometrial biopsy for CE evaluation, as this may enhance the efficacy of the therapeutic approach. The hypothetical link between pelvic endometriosis-related inflammation, its clinical manifestations, and CE requires further investigation. The lack of a noninvasive marker for endometriosis and its grade limits the study results due to reliance on surgical cases, highlighting the need for advanced research in the field of noninvasive diagnostic tools. Trial registration NCT05824507 (registered April 20, 2023).